Deficiencies in physiotherapy education - Johnlyne C. Beenhakker (AOSIS, 1986)
A Study was undertaken to determine a curriculum which would best meet the health care needs of South Africa. From the results of the study, the competencies required for effective physiotherapy practice were determined. When comparing the proposed curriculum to training in South Africa, areas of weakness in the present curricula were established. These areas of deficiency are delineated and the methods for improving physiotherapy education are discussed.